1) a) 4+12x+9x2
4+12x+18
22+12x
2(11+6x)
б) 25-40х+16х2
25-40х+32
57-40х
г) -56а+49а*2+16
-56а+98а+16
42а+16
2(21а+8)
2) a) (y-1)(y+1) б) p^2-9 г) (3x-2)(3x+2) д) (3x)^2-2^2 е) a^2-3^2
y^2-1 (3x)^2-2^2 9x^2-4 a^2-9
в) 4^2-(5y^2) 9x^2-4
16-25y^2
4) a) a3-b3 б) 27a3+8b3
3(a-b) 81a+24b
3(27a+8b)
1) (a - b)² = a² - 2ab + b²
(2х - 1)² = 16
(2х)² - 2 · 2х · (-1) + (-1)² = 16
4х² + 4х + 1 - 16 = 0
4х² + 4х - 15 = 0
D = b² - 4ac = 4² - 4 · 4 · (-15) = 16 + 240 = 256
√D = √256 = 16
х₁ = (-4-16)/(2·4) = (-20)/8 = -2,5
х₂ = (-4+16)/(2·4) = 12/8 = 1,5
ответ: (-2,5; 1,5).
3) (a + b)² = a² + 2ab + b²
25 - (5х + 1)² = 0
25 - ((5х)² + 2 · 5х · 1 + 1²) = 0
25 - (25х² + 10х + 1) = 0
25 - 25х² - 10х - 1 = 0 (умножим обе части уравнения на (-1))
25х² + 10х + 1 - 25 = 0
25х² + 10х - 24 = 0
D = b² - 4ac = 10² - 4 · 25 · (-24) = 100 + 2400 = 2500
√D = √2500 = 50
х₁ = (-10-50)/(2·25) = (-60)/50 = -1,2
х₂ = (-10+50)/(2·25) = 40/50 = 0,8
ответ: (-1,2; 0,8).